The impact of trial characteristics on premature discontinuation of antipsychotics in schizophrenia - Spineli, L; Leucht, S; Cipriani, A; Higgins, J; Salanti, G (2013)
Patient dropout is common in mental health trials. It is important to understand why patients drop out from trials, so that measures can be taken to minimize its occurrence. This research sought to identify trial characteristics that have an impact on premature discontinuation in antipsychotic trials for schizophrenia. Methods: Poisson regression analysis was applied with dropout rate per patient-week as the dependent variable and trial characteristics as independent variables. Multinomial logistic regression analysis was performed to examine whether the same characteristics predict whether patients drop out without providing any outcome data and whether they drop out with sufficient early data for a 'last observation carried forward' analysis to be performed. Results: trials with adequate allocation concealment, double blinding, placebo as control, higher precision, larger trial size, at least three treatment arms, recent publication, conduct in the United States and enrollment of inpatients were all associated with higher dropout rates. Similar factors were associated with whether a patient was more likely to be evaluated at least once, or be excluded entirely from the analysis. However, blinding status did not predict the former type of dropout, and allocation concealment, higher precision and larger sample size, number of arms, recent publication and recruiting inpatient did not predict the latter type of dropout. Conclusions: high dropout rates in antipsychotic trials can be associated with various characteristics, and appears to be particularly associated with use of placebo and study size. © 2013 Elsevier B.V. and ECNP.